Patience Reflected In John Green's The Fault In Our Stars (2012) Novel: An Individual Psychological Approach - Sholihah, Rina Mar'atus; , Dr. Phil. Dewi Chandraningrum, M. Ed; , Titis Setyabudi, S.S. M. Hum (2016)
The object of the research is The Fault in Our Stars novel written by John Green. The major of this study is patience. The objective of the study is to analyze patience reflected in John Green's The Fault in Our Stars based on the structural element and analyze based an individual psychological approach. The research is conducted using descriptive qualitative method. The researcher uses two data sources: primary data source and secondary data source. The primary data source is The Fault in Our Stars novel by John Green. The secondary data sources are the books about individual psychological analysis, references about patience theory and the other sources which are have relation to analysis like some books and internet. The technique of data analysis is descriptive analysis, and the method of the data collection is library research. Based on the analysis, the researcher gets some conclusions. The study shows that the problems faced by the major characters are from they own patience and individual psychology condition. It is proved by the patience to makes the dreams come true and patience in daily life becomes cancer patient between Hazel and Augustus.